miR-200a-3p Attenuates Coronary Microembolization-Induced Myocardial Injury in Rats by Inhibiting TXNIP/NLRP3-Mediated Cardiomyocyte Pyroptosis - Chen, Zhi-Qing; Zhou, You; Chen, Feng; Huang, Jun-Wen; Li, Hao-Liang; Li, Tao; Li, Lang (Frontiers in Cardiovascular Medicine, 2021)
Coronary microembolization (CME) commonly develops as a complication after percutaneous coronary intervention (PCI), and associated inflammation is a leading driver of myocardial damage. Cardiomyocyte loss in the context of ischemic myocardial disease has been linked to inflammatory pyroptotic cell death. Additionally, miR-200a-3p dysregulation has been linked to myocardial ischemia-reperfusion and many other pathological conditions. However, how miR-200a-3p impacts cardiomyocyte pyroptosis in the context of CME remains to be assessed. Herein, a rat model of CME was established via the injection of microembolic spheres into the left ventricle. When myocardial tissue samples from these rats were analyzed, miR-200a-3p levels were markedly decreased, whereas thioredoxin-interacting protein (TXNIP) levels were increased. The ability of miR-200a-3p to directly target TXNIP and to control its expression was confirmed via dual-luciferase reporter assay. Adeno-associated virus serotype 9-pre-miR-200a-3p (AAV-miR-200a-3p) construct transfection was then employed as a means of upregulating this miRNA in CME model rats. Subsequent assays, including echocardiography, enzyme-linked immunosorbent assays (ELISAs), hematoxylin-eosin (H&E) staining, hematoxylin-basic fuchsin-picric acid (HBFP) staining, TdT-mediated dUTP nick-end labeling (TUNEL) staining, immunofluorescence staining, quantitative real-time polymerase chain reaction (qRT-PCR), and Western blotting revealed that miR-200a-3p overexpression inhibited cardiomyocyte pyroptosis and alleviated CME-induced myocardial injury by inhibiting the TXNIP/NOD-like receptor family pyrin domain-containing 3 (NLRP3) pathway. The ability of miR-200a-3p to protect against CME-induced myocardial injury thus highlights a novel approach to preventing or treating such myocardial damage in clinical settings.